Direction: Study the following questions carefully and choose the right answer.
1
If x +  1  = 3, then the value of  3x2 – 4x + 3  is
x x2 – x + 1
» Explain it
C
Given,  x +  1  = 3
x

So,  3x2 – 4x + 3  
x2 – x + 1

⇒  
3x ( x –  4  +  1 )
3 x
 = 
3 [( x +  1 )  –  4 ]
x 3
 
x ( x – 1 +  1 )
x
( x +  1 )  – 1
x

 
=   
3 ( 3  –  4 )
3
 
  =  
3 ( 5 )
3
3 – 1 2

=    5 .
2

Hence, option C is  correct.

2
If x = 2015, y = 2014 and z = 2013, then value of x2 + y2 + z2 – xy – yz – zx is
» Explain it
A
x – y = 2015 – 2014 = 1
y – z = 2014 – 2013 = 1
z – x = 2013 – 2015 = –2

     x2 + y2 + z2 – xy – yz – zx

Numerator & denominator multiplied by 2

=   1 (2x2 + 2y2 + 2z2 – 2xy – 2yz – 2zx)
2

=   1 (x2 + y2 – 2xy + y2 + z2 – 2yz + z2 + x2 – 2zx)
2

=   1 [(x– y)2 + (y – z)2 + (z – x)2]
2

=   1 [1 + 1 + 4] =  1  × 6 = 3
2 2

Hence, option A is correct.

3
If p3 + 3p2 + 3p = 7, then the value of p2 + 2p is
» Explain it
B
p3 + 3p2 + 3p = 7

⇒   p3 + 3p2 + 3p + 1 = 7 + 1 = 8

⇒   (p + 1)3 = (2)3

⇒    p + 1= 2 ⇒ p = 1

∴    p2 + 2p = 1 + 2 × 1 = 1 + 2 = 3.

Hence, option B is correct.

4
If x = p +  1  and y = p –  1  then the value of x4 – 2x2y2 + y4 is
p p
» Explain it
C
x = p +  1  and y = p –  1  
p p

∴    x + y = p +  1  + p –  1  = 2p
p p

x – y = p +  1  – p +  1  =  2
p p p

 x4 – 2x2y2 + y4  =  (x2 – y2)2  =  [(x – y)(x + y)]2     ......(i)

By putting the value of x and y in equation (i), we get

( 2p ×  2 ) 2  = (4)2 = 16.
p  

Hence, option C is correct.

5
If a + b + c = 0, then the value of (a + b – c)2 + (b + c – a)2 + (c + a – b)2 is
» Explain it
C
Given, a + b + c = 0

∴    a + b = – c,   b + c = – a,   c + a = – b

∴   (a + b – c)2 + (b + c – a)2 + (c + a – b)2

⇒   (– c – c)2 + (– a – a)2 + (– b – b)2

⇒   (– 2c)2 + (– 2a)2 + (–2b)2

⇒   4c2 + 4a2 + 4b2 = 4(a2 + b2 + c 2)

Hence, option C is correct.